Dental implants inserted in native bone: Cases series analyses - Riccardo Guidi; Alessandro Viscioni; Frencesco Dattola; Francesco Carinci (Wolters Kluwer Medknow Publications, 2012)
Background: The concept of osseointegration, i.e., the direct anchorage of endosseous implants made of commercially pure or titanium alloy to the bone caused a breakthrough in oral rehabilitation. The identification of factors for long-term survival and success rate are the main goal of the recent literature. Several variables can influence the final result, and in general they are grouped in surgery-, host-, implant-, and occlusion-related factors. Materials and Methods: A retrospective analysis on a large series of dental implants was performed to detect those variables influencing the clinical outcome. In the period between January 2007 and December 2009, 157 patients were operated. A total of 429 implants were inserted. Dental implants are reliable devices to be used in oral rehabilitation. Results: Globally, very few implants were lost at the end of the follow-up period. Slight but significant differences existed among different implants types with regard to peri-implant bone resorption. Conclusion: A better clinical outcome was revealed for Sweden and Martina global implant.